From the depths to the apex: Tracing the organophosphate ester journey through marine food webs - Sala, Berta; Garcia-Garin, Odei; Eljarrat, Ethel (Science of The Total Environment, 2024)
This study explores the behavior of organophosphate esters (OPEs) in different species within marine ecosystems and their potential for bioaccumulation and biomagnification. The concentrations of OPEs were analyzed in marine species (krill (Meganyctiphanes norvegica), jellyfish (Pelagia noctiluca), European sardine (Sardina pilchardus), European anchovy (Engraulis encrasicolus), European hake (Merluccius merluccius), loggerhead turtle (Caretta caretta), European squid (Loligo vulgaris), fin whale (Balaenoptera physalus) and striped dolphin (Stenella coeruleoalba)) from different trophic levels, to understand their distribution and contamination profiles. The study provides insights into the metabolism of OPEs and their biomagnification on species occupying higher trophic levels. The results show that the differences in OPE concentrations among species are influenced by contamination levels at sampling points, as well as species and trophic level characteristics. The study reveals that the sum of OPEs do not exhibit significant biomagnification within the marine food web, with higher trophic level species showing efficient metabolism of these contaminants. However, biomagnification analysis of individual compounds demonstrates that some OPEs, such as tris(2-ethylhexyl) phosphate (TEP), tris(2-butoxyethyl) phosphate (TBOEP), and tris(2-isopropylphenyl) phosphate (T2IPPP) consistently exhibit biomagnification within marine trophic webs, while other show different behaviors depending on the trophic web. The loggerhead turtle shows higher biomagnification for specific OPEs, indicating the influence of diet and direct plastic waste consumption. Furthermore, OPEs prone to metabolism, such as tri-n-butyl phosphate (TNBP) and TBOEP, are present in multiple species across different trophic levels, suggesting a tendency for bioaccumulation. The study highlights the complexity of OPE behavior and the need to evaluate the biomagnification potential of each compound individually. It also emphasizes the toxic effects ...